Legal Status of Third Gender in India with Special Reference to Kanpur Division - Dr. Ganesh Dubey; Priya Jain (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2021)
Liberty, equality, and fraternity, which have been provided by the Constitution to the people of India, are the main goals of social, economic, and political justice. The main purpose of 'justice' is to establish harmony between individual interests and social interests.1 Despite this, there is a section of society that was forced to be deprived of the right to equality due to its unclear gender and sexual identity, but on 15 April The “NALSA Verdict” given by the Supreme Court in 2014 was a landmark judgment for the status of the third gender community and for giving them a clear identity. All the fundamental rights given under the Indian Constitution apply equally to the third gender and provides a clear identity to the third gender community. Through this research paper, along with the legal status of the third gender, the social status has to be observed.